Perhitungan Ongkos Operasi pada Produk Inner Tube Berdasarkan Distribusi Beban Ongkos - Hisyam Al Ghifary; Sukanta Sukanta; Agustian Suseno (AKUNTANSI DEWANTARA, 2021)
In determining the cost of production and sales of a product unit is often faced with problems in making decisions. Determination of the cost of the production unit can be done more quickly and there is a standardized calculation method correctly and correctly. The purpose of this research is to determine and calculate the cost of production per unit of product in a certain amount based on the imposition of production costs. Imposing production costs. The production cost calculation is determined on these production cost components, both by direct and indirect costing in accordance with the organizational structure approach of the company concerned. The result of the research shows that the calculation of the unit cost for the Inner tube product based on the current experience and knowledge of the company is Rp. 15,200 per unit, while the results of research using the distribution method of the production unit cost of Rp. 13,045 per unit. Thus, there is a difference in the unit cost of the product that is 20% cheaper than it is currently in the company